THE INFLUENCE OF ACCOUNTING UNDERSTANDING, WORK EXPERIENCE AND THE ROLE OF INTERNAL AUDIT ON THE QUALITY OF FINANCIAL REPORTS FOR REGIONAL DEVICES WITH INTERNAL CONTROL SYSTEMS AS INTERVENING VARIABLES (Study of Karimun Regency Government) - Saputra, Adi; Satriawan, Bambang; Robin, Robin; Khaddafi, Muammar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
This study aims to determine and analyze the effect of accounting understanding, work experience and the role of internal audit on the financial statements of regional officials with the internal control system as an intervening variable in the Karimun Regency Government. This study uses a quantitative analytic survey method by distributing questionnaires to employees in the OPD (Regional Organizational Organization) Karimun Regency. The population and sample in this study were employees at 33 OPDs in Karimun Regency which consisted of OPD Financial Administration Officers (PPKeu), expenditure treasurers, revenue treasurers and Budget Users (PA) as well as staff who were directly related to the preparation of financial statements totaling 109 people. Data were analyzed using Descriptive Statistical Analysis and Partial Least Square Analysis (SEM-PLS) with Smart PLS 3.0 software program. The results of this study indicate that work experience and the role of internal audit partially have a positive and significant effect on the quality of financial reports, while accounting understanding has a positive and insignificant effect on the quality of financial statements in Karimun Regency and accounting understanding and work experience mediated by the internal control system have a positive effect. and significant to the quality of financial reports, while the role of internal audit mediated by the internal control system has a positive and insignificant effect on the quality of financial reports.